PROPOSAL OF A REVISIONAL SURGERY TO TREAT NON-INSULINOMA HYPERINSULINEMIC HYPOGLICEMIA POSTGASTRIC BYPASS - José SAMPAIO-NETO; Alcides José BRANCO-FILHO; Luis Sérgio NASSIF; André Thá NASSIF; Flávia David João De MASI; Daniele Rezende XIMENEZ (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2015)
Background: Hyperinsulinemic hypoglicemia with severe neuroglycopenic symptoms has been identified as a late and rare complication in patients submitted to Roux-en-Y gastric bypass. However, the potential gravity of its manifestations requires effective treatment of this condition. The absence of treatment makes it necessary to develop more effective clinical or surgical methods. Aim: To present one surgical option to revisional surgery in the treatment of hyperinsulinemic hypoglicemia Methods: The procedure consists in reconstituting alimentary transit through the duodenum and proximal jejunum, while keeping the restrictive part of the gastric bypass. As an additional strategy to maintain weight loss, is realized gastric fundus resection, aiming to suppress ghrelin production more effectively. Results: It was used in three patients with successful results in one year of follow-up. Conclusion: The procedure to reconstruct the food transit through the duodenum and proximal jejunum, keeping the restrictive component of gastric bypass in the treatment of hyperinsulinemic hypoglycemia showed good initial results and validated its application in other cases with this indication.